Serum levels of hyaluronic acid are associated with COPD severity and predict survival. Issue 3 (7th March 2019) - Papakonstantinou, Eleni; Bonovolias, Ioannis; Roth, Michael; Tamm, Michael; Schumann, Desiree; Baty, Florent; Louis, Renaud; Milenkovic, Branislava; Boersma, Wim; Stieltjes, Bram; Kostikas, Konstantinos; Blasi, Francesco; et al.
Hyaluronic acid (HA) and its degradation products play an important role in lung pathophysiology and airway remodelling in chronic obstructive pulmonary disease (COPD). We investigated if HA and its degrading enzyme hyaluronidase (HYAL)-1 are associated with COPD severity and outcome. Serum HA was assessed in a discovery cohort of 80 COPD patients at stable state and exacerbations. HA, HYAL-1 and HYAL-1 enzymatic activity were evaluated at stable state, exacerbations and 4 weeks after exacerbations in 638 COPD patients from the PROMISE validation cohort. In the discovery cohort, serum HA was higher at exacerbations compared with the stable state (p=0.015). In the validation cohort, HA was higher at moderate and severe exacerbations than at baseline (p<0.001), and remained higher after 4 weeks (p<0.001). HA was strongly predictive for overall survival since it was associated with time to death (p<0.001) independently of adjusted Charlson score, annual exacerbation rate and BODE (body mass, airflow obstruction, dyspnoea, exercise capacity) index. Serum HYAL-1 was increased at moderate (p=0.004) and severe (p=0.003) exacerbations, but decreased after 4 weeks (p<0.001). HYAL-1 enzymatic activity at stable state was inversely correlated with FEV1 % pred (p=0.034) and survival time (p=0.017). Serum HA is associated with COPD severity and predicts overall survival. Degradation of HA is associated with airflow limitation and impairment of lung function. Serum hyaluronic acid (HA) is associated with COPD severity, outcome and predicts overall survival. Enzymatic degradation of HA is associated with airflow limitation and impairment of lung function. http://ow.ly/COl830n2IcQ